2010
DOI: 10.1186/1471-2318-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic treatment of elderly patients - a prospective observational study with follow-up over a two year period

Abstract: BackgroundVery little is known about the range of diagnoses, course of treatment and long-term outcome in elderly patients who choose to receive homeopathic medical treatment. We investigated homeopathic practice in an industrialised country under everyday conditions.The aim of the study was to determine the spectrum of diagnoses and treatments, as well as to describe the course of illness over time among older patients who chose to receive homeopathic treatment.MethodsIn this subgroup analysis of a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…Among a representative population of older adults we showed that those with hip fracture had higher illness burden (15,16). They were more likely to have ADL dependency and IADL difficulty and were more likely to have helpers.…”
Section: Discussionmentioning
confidence: 91%
“…Among a representative population of older adults we showed that those with hip fracture had higher illness burden (15,16). They were more likely to have ADL dependency and IADL difficulty and were more likely to have helpers.…”
Section: Discussionmentioning
confidence: 91%
“…[16] Causticum Hah is a homeopathic medicinal preparation given for chronic rheumatological conditions and some of the respiratory symptoms. [6] We managed this as a case of alcohol intoxication as the homeopathic medicinal preparation was having 90% vol/vol of alcohol and he had consumed it in excessive amount (1350 mL).…”
Section: Discussionmentioning
confidence: 99%
“…The patients who seek homeopathic treatment are primarily those suffering from long-standing, chronic diseases. It is based on the “principle of similars,” where by highly diluted preparations of substances that cause symptoms in healthy individuals are used to stimulate healing in patients who have similar symptoms when ill.[1] Some of these medicines may have considerable risk of severe side effects. We hereby report an unusual case of refractory metabolic acidosis after homeopathic medicinal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In homeopathy, highlydiluted preparations of substances that cause symptoms in healthy individuals are used to stimulate healing reactions in patients who display similar symptoms when ill [1]. Homeopathy is applied to treat various diseases and conditions such as cancer [2][3][4][5][6][7], allergies [8][9][10][11][12][13][14][15][16], mood disorders [17][18][19], cardiovascular diseases (CVD) [20,21], osteoarthritis [22], hemophilia [23], headache [24,25], and pain [26,27].…”
Section: Introductionmentioning
confidence: 99%